Students Mathematical Representation and Communication Ability in Mathematics Problem Solving - Pieter Zakarias Tupamahu; Tanwey Gerson Ratumanan; Christina Laamena (Didaktik Matematika, 2023)
In learning mathematics, representation and communication ability are required by students to solve problems. The ability to represent is crucial for students to simplify the learning process, while students who have good mathematical communication abilities can easily solve a problem. This study applied a sequential mixed methods approach. Quantitative data was obtained from the results of the written test, then the ability of mathematical representation and communication in solving problems on linear program material was analyzed qualitatively. The participants of this study were 59 students from one of the senior high schools in Ambon, Indonesia. The research phase was begun with students being asked to solve mathematics problems and then researchers analyze representation and written communication ability. The largest percentage of students' results on the test was in the very low category of mathematical representation and communication ability. The results showed that students who had good representation and communication abilities would be able to solve problems. There were significant correlations and a very strong correlation between mathematical representation and communication ability with a Pearson Correlation coefficient of 0.915. After obtaining the test result, subjects were selected based on the category of ability to conduct interviews. Based on the results of the interview, the mathematical representation ability that the subject uses well will directly involve mathematical communication skills well, and vice versa.